Plataforma educativa fle3 y su influencia en la interacción entre estudiantes y docente de la Unidad Educativa Replica Eugenio Espejo del cantón Babahoyo, de la Provincia de Los Ríos - Aguirre Cruz, Marelin Andreina (2020)
This research paper entitled “FLE3 EDUCATIONAL PLATFORM AND ITS INFLUENCE ON INTERACTION BETWEEN STUDENTS AND TEACHERS OF THE REPLICA EDUCATIONAL UNIT ‟EUGENIO ESPEJO” OF THE CANTÓN BABAHOYO, OF THE PROVINCE OF LOS RIOS, aims to determine the influence of the platform fle3 in the interaction between students and teacher of the educational unit 'Eugenio mirror' replica of the Babahoyo canton, of the province of the rivers, during the 2019-2020 school year. Bibliographic, field and diagnostic research was used with the deductive and inductive method, its respective survey applied to teachers and students; With a sample of 140 participants, the research results identified the variables involved in the hypothesis. Conclusions were established where the educational platforms for interaction, have a relationship with education because it allows to improve participation and interaction in the teaching-learning process, and provide interest in learning, so in this way the student does not feel bored and be able to build their own knowledge, recommending teachers implement interactive tools so that they arouse interest in learning in the student and the teaching-learning process is of quality.